Large Methane Emission Fluxes Observed From Tropical Wetlands in Zambia. Issue 6 (10th June 2022) - Shaw, Jacob T.; Allen, Grant; Barker, Patrick; Pitt, Joseph R.; Pasternak, Dominika; Bauguitte, Stéphane J.‐B.; Lee, James; Bower, Keith N.; Daly, Michael C.; Lunt, Mark F.; Ganesan, Anita L.; Vaughan, Adam R.; et al.
Abstract: Methane (CH4 ) is a potent greenhouse gas with a warming potential 84 times that of carbon dioxide (CO2 ) over a 20‐year period. Atmospheric CH4 concentrations have been rising since the nineteenth century but the cause of large increases post‐2007 is disputed. Tropical wetlands are thought to account for ∼20% of global CH4 emissions, but African tropical wetlands are understudied and their contribution is uncertain. In this work, we use the first airborne measurements of CH4 sampled over three wetland areas in Zambia to derive emission fluxes. Three independent approaches to flux quantification from airborne measurements were used: Airborne mass balance, airborne eddy‐covariance, and an atmospheric inversion. Measured emissions (ranging from 5 to 28 mg m −2 hr −1 ) were found to be an order of magnitude greater than those simulated by land surface models (ranging from 0.6 to 3.9 mg m −2 hr −1 ), suggesting much greater emissions from tropical wetlands than currently accounted for. The prevalence of such underestimated CH4 sources may necessitate additional reductions in anthropogenic greenhouse gas emissions to keep global warming below a threshold of 2°C above preindustrial levels. Plain Language Summary: Methane (CH4 ) is a powerful greenhouse gas. The more CH4 in the atmosphere, the greater the amount of warming. CH4 is emitted naturally by many sources, such as wetlands, but is also emitted by many human activities, such as fossil fuel use, waste treatment, and farming. Tropical wetlands are thought to account for roughly one‐fifth of the global CH4 emissions, but studies on tropical wetlands in Africa are extremely rare. We measured CH4 emissions from three separate wetlands in Zambia (southern Africa) and found that models were estimating much lower CH4 emissions. If more CH4 is being emitted by the many other African wetlands than currently thought, then we may have overestimated the amount of CH4 that humans can yet emit before reaching 2°C of global warming, and failing the promises set out in the Paris Agreement. Key Points: Quantification of the first methane emission fluxes from Zambian wetlands using world‐first airborne survey data recorded over Zambia Intercomparison of, and guidance on, the use of three independent approaches for flux quantification from aircraft surveys Wetland methane fluxes were observed to be significantly greater than those simulated by Global Carbon Project land surface models